ROLE OF ADULT AND NON-FORMAL EDUCATION PROGRAMMES IN PROMOTING SUSTAINABLE PEACE, SECURITY AND NATIONAL DEVELOPMENT IN NIGERIA - BABANZARA , UMMU HASSAN (Sokoto Educational Review, 2025)
This paper examined the role of Adult and Non-formal education in building a sustainable national peace, security and development in Nigeria. Adult and Non-Formal Education aims at preventing violent conflict in advance and educating individuals and societies for peaceful and harmonious co-existence which in turn promotes tolerance, non-violence, equity, respect for one another and social justice. The study employed systematic method of review. Secondary data was used in the study. Literate individuals and societies resolve conflicts peacefully without resorting to violence or war which adversely affects the socio-economic, political and cultural life of the people and development of any nation. This type of education aims to prevent future conflicts and educate individuals and communities to coexist peacefully and harmoniously, promoting values like tolerance, non-violence, equality, and respect. The findings of the study revealed that educated individuals and societies are more likely to resolve disputes without resorting to violence, which negatively impacts society, politics, culture, and development. In Nigeria, ethnic tensions sometimes arise due to underdevelopment, political, social, and economic disparities, leading to violent clashes and conflicts. This research examines various aspects of adult and non-formal education, such as its relation to sustainable peace and security in Nigeria, sustainable national development, and peace for sustainable development. It also identifies challenges in adult and non-formal education and proposes strategies to achieve national peace, security, and development.